Mycoplasma genitalium in women with lower genital tract inflammation. Issue 1 (8th October 2008) - Moi, H; Reinton, N; Moghaddam, A
Abstract : Objectives: To examine the prevalence of Mycoplasma genitalium in a large number of female patients attending a sexually transmitted infections (STI) clinic and to determine if there is an association with signs or symptoms of lower genital tract inflammation (LGTI). Methods: Altogether, 7646 female patients who had symptoms or microscopic signs of LGTI or were perceived to be at high risk of exposure to an STI were tested for both M genitalium and Chlamydia trachomatis . Urethral and cervical smears were examined quantitatively for polymorphic mononuclear leucocytes (PMNLs). Results: The prevalence of C trachomatis and M genitalium was 10.1% and 4.5%, respectively. We found a clear association between detecting M genitalium in first void urine (FVU) of patients and signs of urethral inflammation. The strongest association was between detecting M genitalium in FVU and number of PMNLs in urethral smears (n = 6790; OR 2.1; 95 % CI 1.5 to 2.9). The association was less significant between detecting M genitalium in cervical swabs and the number of PMNLs in urethral smears (n = 6785; OR 1.4; 95% CI 1.1 to 1.9), although cervical swabs gave higher sensitivity than FVU in detecting M genitalium (86% vs 62%). C trachomatis detection in FVU and cervical swabs was highly concordant and both significantly associated with urethritis (n = 6790; OR 3.6; 95% CI 3.0 to 4.4). Conclusions: This data support the hypothesis that M genitalium causes urethritis in women and that M genitalium infection of the genitourinary tract leads to different clinical manifestations depending on whether the site of infection is the urethral or the cervical epithelium.